Post-treatment method for flame synthesis of titanium niobium oxide powder and application
After the preparation of titanium niobium oxide powder by flame synthesis, combined with the post-treatment process of annealing and crystal-regulating phase and ball grinding, the problems of high energy consumption and difficult to control composition uniformity in traditional methods are solved, and the preparation of powder with high purity, stable structure and precise particle size distribution is achieved, and the process flow is simplified.
Patent Information
- Application Number
- CN202510314857.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The traditional titanium niobium oxide powder preparation method has problems such as high energy consumption, long production cycle, and difficult to control composition uniformity. The powder prepared by flame synthesis method requires post-treatment to improve performance and purity, but the existing post-treatment process is complex and it is difficult to accurately control the powder performance.
After the flame synthesis method is used to prepare titanium niobium oxide powder, the annealing and crystallization phase and ball grinding process are carried out under an oxygen atmosphere to remove impurities, achieve uniform crystallization and stable crystal phase of the oxide, accurately control the particle size distribution, and reduce process complexity.
The purity and structural stability of titanium niobium oxide powder are improved, precise control of particle size distribution is achieved, the post-treatment process is simplified, and the performance and applicability of the powder are improved.
Smart Images

Figure CN119841349A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium niobium oxides, and in particular to a post-processing method and application of flame-synthesized titanium niobium oxide powders. Background Art
[0002] Titanium niobium oxide (TNO) is a composite material with excellent chemical stability and high temperature resistance, which is widely used in the fields of electronics, catalysis, batteries and superconductivity. Traditional preparation methods have problems such as high energy consumption, long production cycle, and difficult control of component uniformity. The patent with publication number CN110465257B discloses a nanoparticle swirl flame atomization doping synthesis system and its synthesis method, in which the primary air and fuel gas enter the swirl burner through adjacent air flow channels to form a swirl airflow, and the fuel gas is ignited to form a swirl flame. The metal precursor solution is atomized by a swirl impact atomizer and then enters the swirl flame to burn to produce a nanoparticle flow, which is diluted and cooled before collection. Therefore, the flame synthesis method, with its advantages of fast speed, low energy consumption, simple equipment, high purity and easy industrial production, shows great potential in the preparation of titanium niobium oxide powder, and is expected to overcome the shortcomings of traditional methods and improve product performance. However, the patent does not mention the post-processing process after the powder is prepared by the flame synthesis method. In fact, the post-processing process of the powder prepared by the flame synthesis method is crucial to improving the performance and applicability of the powder after the rapid combustion reaction.
[0003] The post-processing process can remove impurities and unreacted raw materials generated during the combustion process, improve the purity of the powder, improve the morphology and structure of the powder, enhance its dispersibility and stability in the final product, and adjust the particle size distribution of the powder through subsequent processing steps such as grinding and grading to meet the needs of different application fields. However, there are many problems with the current traditional post-processing process, including: it is difficult to completely remove impurities and unreacted materials, which affects the purity of the final product; precise control of particle size distribution requires sophisticated operations and equipment, which increases the complexity of the process to a certain extent; and it is difficult to accurately control the powder properties of titanium niobium oxide through post-processing. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a post-treatment method and application of flame-synthesized titanium niobium oxide powder. By post-treating the flame-synthesized titanium niobium oxide powder, including an annealing crystal phase adjustment process and a ball milling crushing process under an oxygen atmosphere, not only can the impurities in the titanium niobium oxide powder be removed and the purity of the powder be improved, but also the uniform crystallization and stable crystal phase of the oxide can be achieved, the morphology and structure of the powder can be improved, the precise control of the powder particle size distribution can be achieved, and the complexity of the post-treatment process can be reduced.
[0005] The purpose of the present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a post-treatment method for flame-synthesized titanium niobium oxide powder, comprising the following steps: Step 1: The titanium niobium oxide powder prepared by flame synthesis is an amorphous powder with a particle size D50 of 0.9-3 μm and a D90 of 10-15 μm; the powder is annealed in an oxygen atmosphere at a temperature of 1000-1200° C. for a holding time of 2-3 h to obtain a monoclinic phase powder; Step 2: ball milling to crush the hollow sphere particles in the monoclinic phase powder, with a ball-to-material ratio of 1:1-3 and a ball milling speed of 100-500 r / min; Step 3: Perform filter pressing and drying to obtain post-treated titanium niobium oxide powder.
[0006] The flame synthesis method is to add metal precursors and organic additives to organic fuel, and then obtain titanium niobium oxide powder (TiNb 2 O 7 ), since the titanium niobium oxide powder obtained by the flame synthesis method is an amorphous powder and contains organic impurities and unreacted metal precursor raw materials, it cannot be directly used in lithium batteries. The present invention is a post-treatment process for titanium niobium oxide powder prepared by the flame synthesis method. Through the annealing crystal phase adjustment process in an oxygen atmosphere, the annealing condition parameters (including annealing temperature, time, etc.) are controlled, which can not only remove impurities in the titanium niobium oxide powder and improve the purity of the powder, but also can transform the amorphous powder into a monoclinic m-TNO phase (Monoclinic-TiNb 2 O 7 ) powder, achieve uniform crystallization and stable crystal phase of oxide, and improve the morphology and structure of powder.
[0007] However, the annealing phase will go through a high temperature process. The high temperature will reduce the potential barrier between the particles, thereby promoting the agglomeration of titanium niobium oxide powder. The agglomeration between the crystals will form hollow spherical particles. Ball milling can break up the titanium niobium oxide powder agglomerates, but it is necessary to select appropriate ball milling parameters (including ball-to-material ratio, ball milling speed, etc.) to avoid particle damage while dispersing the particles, and to achieve precise control of the powder particle size distribution.
[0008] Preferably, the impurity content of the titanium niobium oxide powder obtained by the flame synthesis method is 3-6wt%.
[0009] The titanium niobium oxide powder produced by the flame synthesis method has a large particle size, a large gap between the particle sizes D50 and D90, and an uneven particle size distribution. Through the coordinated control of annealing and ball milling, the titanium niobium oxide powder can have a stable crystal phase while having a smaller particle size and a concentrated particle size distribution.
[0010] Preferably, the heating rate of the annealing is 10-20°C / min.
[0011] Preferably, the oxygen flow rate during the annealing is 3-5 L / min.
[0012] Preferably, the annealing conditions are: heating from room temperature to 1000° C. at a heating rate of 10-20° C. / min, keeping the temperature for 2-3 hours, and then cooling to room temperature.
[0013] Preferably, the ball milling time is 1-3h.
[0014] Preferably, the pressure of the filter pressing is 0.2-0.5 MPa, and the time is 20-60 min; and the medium of the filter pressing is ethanol.
[0015] Preferably, the drying temperature is 60-150° C. and the drying time is 1-4 hours.
[0016] Preferably, the particle size D50 of the post-treated titanium niobium oxide powder is 300-600 nm, and D90 is 800-1200 nm.
[0017] In a second aspect, the present invention also provides a use of post-treated titanium niobium oxide powder in a lithium battery.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention performs post-treatment on titanium niobium oxide prepared by flame synthesis, which can effectively remove impurities and unreacted products in titanium niobium oxide powder, obtain monoclinic phase powder, and achieve precise control of powder particle size distribution, and reduce the complexity of post-treatment process; (2) The present invention provides a post-treatment process for flame-synthesized titanium niobium oxide powder, which has the advantages of simple post-treatment process, stable crystal phase, and precise control of powder particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 These are the XRD diagrams of the flame synthesis powder, the annealed powder and the dried powder of the present invention.
[0020] Figure 2 This is the particle size distribution diagram of titanium niobium oxide powder I prepared by the flame synthesis method of the present invention.
[0021] Figure 3 This is a particle size distribution diagram of titanium niobium oxide powder I prepared by flame synthesis method of the present invention after post-treatment in Example 1. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0023] 1. Post-treatment of flame synthesized titanium niobium oxide powder: Step 1: Titanium niobium oxide powder prepared by flame synthesis method (flame synthesis method reference patent: publication number CN110465257B, invention name is a nanoparticle swirl flame atomization doping synthesis system and synthesis method thereof): Select and weigh appropriate amounts of titanium and niobium metal nitrates as metal precursors, select and weigh organic additives and organic fuels, and make the volume ratio of organic additives to organic fuels be 1: (4-9), the organic additives include 2-ethylhexanoic acid or cyclohexane acid, and the organic fuel includes ethanol, butanol or a xylene mixture; the metal nitrates, organic additives and organic fuels are uniformly mixed to obtain a metal precursor solution, wherein the metal ion concentration is less than or equal to 0.5 mol / L and greater than or equal to 0.1 mol / L, and the metal precursor solution and atomizing gas (compressed air) are respectively introduced into a cyclonic impact atomizer through a precursor liquid inlet and an atomizing gas inlet, so that the precursor solution is atomized by the atomizing gas into metal precursor droplets with a particle size of less than or equal to 30 μm, and the droplet size is adjusted by the relative height of the precursor liquid outlet and the atomizing gas outlet. Metal precursor droplets enter the stable swirl flame, are ignited by the swirl flame, and burn to synthesize nanoparticles; the nanoparticles ascend with the combustion flue gas to form a high-temperature nanoparticle flow, and titanium niobium oxide powder with a particle size D50 of 0.9-3μm and D90 of 10-15μm is obtained. The impurities in the powder are mainly organic impurities and a small amount of Na, Si, P, etc. (Na, Si, P and other impurities are contained in the purchased raw materials themselves, and the amount will range from tens to hundreds of ppm), and the impurity content is 3-6wt%.
[0024] The titanium niobium oxide powder collected from the front end of the process is dried in an explosion-proof oven set at 80-180°C. The titanium niobium oxide powder is annealed to remove carbon and adjust the crystal phase. A corundum pot is used. Each can is filled with 200-500g of titanium niobium oxide. The corundum pot is covered, but a gap is left to allow the surrounding oxygen to enter the corundum pot for annealing. The heating rate during the annealing process is 10-20°C / min, the temperature is raised to 1000-1200°C, and the temperature is kept for 2-3h. An oxygen atmosphere is used while heating and keeping the temperature, and the oxygen flow rate is 3-5 L / min. After annealing, it is cooled to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0025] Step 2: The annealing phase will go through a high temperature process. The high temperature will reduce the potential barrier between the particles, thereby promoting the agglomeration of titanium niobium oxide powder. Ball milling can break up some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, fill a small amount of zirconium beads at the bottom of the ball mill, and then load the powder with a ball-to-material ratio of 1:1-3. Tighten the ball mill to prevent the rotating internal powder from spilling out; then perform ball milling with a ball mill speed of 100-500r / min and a ball mill running time of 1-3h.
[0026] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter the ball-milled titanium niobium oxide powder, the filtration pressure is 0.2-0.5MPa, the filter paper filtration accuracy is 0.45μm, and the time is 20-60min; when filtering 1-2 tanks, set the pressure to 0.2-0.5MPa, the filter press time is 20-30min, and the filter press is completed when the water loss rate is <16%; when filtering 3-4 tanks, set the pressure to 0.2-0.5MPa, the filter press time is 30-60min, and the filter press is completed when the water loss rate is <20%, and collect the anhydrous ethanol flowing out of the filter press. After the filtration is completed, turn off the air compressor before opening the filter tank to ensure that there is no pressure in the filter tank; open the filter tank and check whether there are large particles of powder in the screen. If there are, use scrapers, brushes and other tools to crush them and sieve them manually; add a stainless steel filter membrane on the filter paper to prevent the filter paper material from falling and contaminating the powder.
[0027] Step 4: Drying the titanium niobium oxide powder: Put the titanium niobium oxide powder with a water loss rate of less than 20% obtained after filter pressing (if the water loss rate of the powder is greater than 20%, cover it with a lid, place it in the air for one hour, and then re-measure the water loss rate) into an oven for drying. The powder needs to be flattened with a scraper. The drying temperature is 60-150°C and the time is 1-4h. Take 20g of the dried powder for water loss rate test and whiteness test. A water loss rate of 0% is qualified, and a whiteness of more than 80 is qualified.
[0028] Step 5: Packing the titanium niobium oxide powder: Use a vacuum device to fill the powder and then vacuum pack it. The outer layer is protected with nitrogen. Pay attention to whether the vacuum packaging and nitrogen packaging are intact and whether there is any leakage.
[0029] 2. Lithium battery: The titanium niobium oxide powder obtained after post-treatment is used as a negative electrode material to make a lithium battery.
[0030] Example 1 Step 1: If Figure 2As shown, the titanium niobium oxide powder Ⅰ (amorphous powder, particle size D50 is 1362.42 nm, D90 is 11029.21 nm, impurity content is 5wt%) collected from the front end of the process by flame synthesis was dried and dried at 120°C. The titanium niobium oxide powder was annealed to remove carbon and adjust the crystal phase. A corundum pot was used, and 300g of titanium niobium oxide was filled in each can. The corundum pot was covered, but a gap was left to allow the surrounding oxygen to enter the corundum pot for annealing. During the annealing process, the heating rate was 10°C / min, the temperature was raised to 1000°C, and the temperature was kept for 2h. An oxygen atmosphere was used while heating and keeping the temperature, and the oxygen flow rate was 3L / min. After annealing, it was cooled to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0031] Step 2: Ball milling is used to crush some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, a small amount of zirconium beads is filled at the bottom of the ball mill, and then the powder is loaded with a ball-to-material ratio of 1:1. The ball mill is tightened to prevent the powder inside from spilling out during rotation. Then, ball milling is performed with a ball mill speed of 500 r / min and a ball mill operation time of 1 h.
[0032] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, filtration is 1 tank, the filtration time is 30min, the filtration is completed when the water loss rate is 10%, and the anhydrous ethanol flowing out of the filtration is collected.
[0033] Step 4: Drying the titanium niobium oxide powder: The titanium niobium oxide powder with a water loss rate of 10% obtained after filter pressing is put into an oven for drying. The powder needs to be flattened with a scraper, baked in an oven at 70°C for 30 minutes, broken with a glass rod, and then heated to 120°C for 1.5 hours. Take 20g of the dried powder for water loss rate test and whiteness test. The water loss rate is 0%, the whiteness is 85, and the BET test is 2.705m 2 / g, such as Figure 3 Shown is the particle size distribution of the post-treated powder.
[0034] like Figure 1 The XRD patterns of the flame synthesis powder (TiNbO powder Ⅰ obtained by flame synthesis), the annealed powder (monoclinic phase powder obtained in step 1), and the dried powder (dried powder obtained in step 4) are shown. 2 O 7 ) Comparison with the standard XRD spectra shows that the flame synthesis powder can obtain the m-TNO phase after annealing, and the powder obtained after ball milling and drying still maintains a stable crystalline phase.
[0035] Example 2 Step 1: Dry the titanium niobium oxide powder I obtained by flame synthesis collected from the front end of the process, and set the drying temperature to 120°C. Anneal the titanium niobium oxide powder to remove carbon and adjust the crystal phase. Use a corundum pot, fill each can with 300g of titanium niobium oxide, cover the corundum pot, but leave a gap to allow the surrounding oxygen to enter the corundum pot, and anneal. During the annealing process, the heating rate is 20°C / min, the temperature is raised to 1000°C, and the temperature is kept for 2h. While heating and keeping the temperature, an oxygen atmosphere is used, and the oxygen flow rate is 5L / min. After annealing, it is cooled to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0036] Step 2: Use ball mill to crush some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, fill a small amount of zirconium beads at the bottom of the ball mill, and then load the powder with a ball-to-material ratio of 1:1. Tighten the ball mill to prevent the powder from spilling out of the rotating interior. Then, perform ball milling with a speed of 300 r / min and a running time of 2 h.
[0037] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, filtration is 1 tank, the filtration time is 30min, the filtration is completed when the water loss rate is 11%, and the anhydrous ethanol flowing out of the filtration is collected.
[0038] Step 4: Drying the titanium niobium oxide powder: The titanium niobium oxide powder with a water loss rate of 11% obtained after filter pressing is put into an oven for drying. The powder needs to be flattened with a scraper, baked in an oven at 70°C for 30 minutes, broken with a glass rod, and then heated to 120°C for 1.5 hours. Take 20g of the dried powder for water loss rate test and whiteness test. The water loss rate is 0%, the whiteness is 86, and the BET test is 2.370m 2 / g.
[0039] Example 3 Step 1: Dry the titanium niobium oxide powder I obtained by flame synthesis collected from the front end of the process, and set the drying temperature to 120°C. Anneal the titanium niobium oxide powder to remove carbon and adjust the crystal phase. Use a corundum pot, fill each can with 1000g of titanium niobium oxide, cover the corundum pot, but leave a gap to allow the surrounding oxygen to enter the corundum pot, and anneal. During the annealing process, the heating rate is 20°C / min, the temperature is raised to 1000°C, and the temperature is kept for 2h. While heating and keeping the temperature, an oxygen atmosphere is used, and the oxygen flow rate is 5L / min. After annealing, it is cooled to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0040] Step 2: Use ball mill to crush some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, fill a small amount of zirconium beads at the bottom of the ball mill, and then load the powder with a ball-to-material ratio of 1:1. Tighten the ball mill to prevent the powder from spilling out of the rotating interior. Then, perform ball milling with a speed of 300 r / min and a running time of 2 h.
[0041] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, 4 tanks are filtered, the filtration time is 60min, the filtration is completed when the water loss rate is 21%, and the anhydrous ethanol flowing out of the filtration is collected.
[0042] Step 4: Dry the titanium niobium oxide powder: Cover the titanium niobium oxide powder with a water loss rate of 21% obtained after filter pressing with a lid, place it in the air for one hour, and re-measure the water loss rate to be 18%. Put it into the oven for drying. The powder needs to be flattened with a scraper, and then baked in the oven at 70℃ for 30 minutes, broken with a glass rod, and then heated to 120℃ and baked for 1.5 hours; take 20g of the dried powder for water loss rate test and whiteness test, the water loss rate is 0%, the whiteness is 86, and the BET test is 2.821m 2 / g.
[0043] Example 4 Step 1: Dry the titanium niobium oxide powder II (amorphous powder, particle size D50 is 919.31 nm, D90 is 11486.46 nm, impurity content is 4wt%) collected from the front end of the process, and set the drying temperature to 120°C. Anneal the titanium niobium oxide powder to remove carbon and adjust the crystal phase. Use a corundum pot, fill each can with 300g of titanium niobium oxide, cover the corundum pot, but leave a gap to allow the surrounding oxygen to enter the corundum pot, and anneal. During the annealing process, the heating rate is 10°C / min, the temperature is raised to 1000°C, and the temperature is kept for 2h. While heating and keeping the temperature, an oxygen atmosphere is used, and the oxygen flow rate is 3L / min. After annealing, cool to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0044] Step 2: Ball milling is used to crush some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, a small amount of zirconium beads is filled at the bottom of the ball mill, and then the powder is loaded with a ball-to-material ratio of 1:1. The ball mill is tightened to prevent the powder inside from spilling out during rotation. Then, ball milling is performed with a ball mill speed of 460 r / min and a ball mill operation time of 1 h.
[0045] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, filtration is 1 tank, the filtration time is 30min, the filtration is completed when the water loss rate is 10%, and the anhydrous ethanol flowing out of the filtration is collected.
[0046] Step 4: Drying the titanium niobium oxide powder: The titanium niobium oxide powder with a water loss rate of 10% obtained after filter pressing is put into an oven for drying. The powder needs to be flattened with a scraper, baked in an oven at 70°C for 30 minutes, broken with a glass rod, and then heated to 120°C for 1.5 hours. Take 20g of the dried powder for water loss rate test and whiteness test. The water loss rate is 0%, the whiteness is 86, and the BET test is 2.775m 2 / g.
[0047] Comparative Example 1 The difference from Example 1 is that the annealing temperature is too low, which is 500°C.
[0048] Step 1: Dry the titanium niobium oxide powder I obtained by flame synthesis collected from the front end of the process, and set the drying temperature to 120°C. Anneal the titanium niobium oxide powder to remove carbon and adjust the crystal phase. Use a corundum pot, fill each can with 300g of titanium niobium oxide, cover the corundum pot, but leave a gap to allow the surrounding oxygen to enter the corundum pot, and anneal. During the annealing process, the heating rate is 10°C / min, the temperature is raised to 500°C, and the temperature is kept for 2h. While heating and keeping the temperature, an oxygen atmosphere is used, and the oxygen flow rate is 3L / min. After annealing, it is cooled to room temperature to obtain a powder, but the powder is not a monoclinic phase, and the purity is 99.9%.
[0049] Step 2: Ball milling to crush the powder. First, fill a small amount of zirconium beads at the bottom of the ball mill, then load the powder with a ball-to-material ratio of 1:1. Tighten the ball mill to prevent the powder from spilling out of the rotating interior. Then, perform ball milling with a speed of 500 r / min and a running time of 1 h.
[0050] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, filtration is 1 tank, the filtration time is 30min, the filtration is completed when the water loss rate is 10%, and the anhydrous ethanol flowing out of the filtration is collected.
[0051] Step 4: Drying the titanium niobium oxide powder: The titanium niobium oxide powder with a water loss rate of 10% obtained after filter pressing is put into an oven for drying. The powder needs to be flattened with a scraper, baked in an oven at 70°C for 30 minutes, broken with a glass rod, and then heated to 120°C for 1.5 hours. Take 20g of the dried powder for water loss rate test and whiteness test. The water loss rate is 0%, the whiteness is 84, and the BET test is 5.981m 2 / g.
[0052] Comparative Example 2 The difference from Example 1 is that the oxygen flow rate during annealing is too large, and the oxygen flow rate is 10 L / min.
[0053] Step 1: Dry the titanium niobium oxide powder I obtained by flame synthesis collected from the front end of the process, and set the drying temperature to 120°C. Anneal the titanium niobium oxide powder to remove carbon and adjust the crystal phase. Use a corundum pot, fill each can with 300g of titanium niobium oxide, cover the corundum pot, but leave a gap to allow the surrounding oxygen to enter the corundum pot, and anneal. During the annealing process, the heating rate is 10°C / min, the temperature is raised to 1000°C, and the temperature is kept for 2h. While heating and keeping the temperature, an oxygen atmosphere is used, and the oxygen flow rate is 10L / min. After annealing, cool to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0054] Step 2: Ball milling is used to crush some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, a small amount of zirconium beads is filled at the bottom of the ball mill, and then the powder is loaded with a ball-to-material ratio of 1:1. The ball mill is tightened to prevent the powder inside from spilling out during rotation. Then, ball milling is performed with a ball mill speed of 500 r / min and a ball mill operation time of 1 h.
[0055] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, filtration is 1 tank, the filtration time is 30min, the filtration is completed when the water loss rate is 10%, and the anhydrous ethanol flowing out of the filtration is collected.
[0056] Step 4: Drying the titanium niobium oxide powder: The titanium niobium oxide powder with a water loss rate of 10% obtained after filter pressing is put into an oven for drying. The powder needs to be flattened with a scraper, baked in an oven at 70°C for 30 minutes, broken with a glass rod, and then heated to 120°C for 1.5 hours. Take 20g of the dried powder for water loss rate test and whiteness test. The water loss rate is 0%, the whiteness is 85, and the BET test is 1.567m 2 / g.
[0057] Comparative Example 3 The difference from Example 1 is that the ball-to-material ratio during ball milling is 1:20.
[0058] Step 1: Dry the titanium niobium oxide powder I obtained by flame synthesis collected from the front end of the process, and set the drying temperature to 120°C. Anneal the titanium niobium oxide powder to remove carbon and adjust the crystal phase. Use a corundum pot, fill each can with 300g of titanium niobium oxide, cover the corundum pot, but leave a gap to allow the surrounding oxygen to enter the corundum pot, and perform annealing. During the annealing process, the heating rate is 10°C / min, the temperature is raised to 1000°C, and the temperature is kept for 2h. While heating and keeping the temperature, an oxygen atmosphere is used, and the oxygen flow rate is 3L / min. After annealing, it is cooled to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0059] Step 2: Ball milling to crush some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, fill a small amount of zirconium beads at the bottom of the ball mill, and then load the powder with a ball-to-material ratio of 1:20. Tighten the ball mill to prevent the powder from spilling out of the rotating interior; then perform ball milling with a ball mill speed of 500 r / min and a ball mill running time of 1 h.
[0060] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, filtration is 1 tank, the filtration time is 30min, the filtration is completed when the water loss rate is 10%, and the anhydrous ethanol flowing out of the filtration is collected.
[0061] Step 4: Drying the titanium niobium oxide powder: Put the titanium niobium oxide powder with a water loss rate of 10% obtained after filter pressing into an oven for drying. The powder needs to be flattened with a scraper, baked in an oven at 70°C for 30 minutes, broken with a glass rod, and then heated to 120°C for 1.5 hours. Take 20g of the dried powder for water loss rate test and whiteness test. The water loss rate is 0%, the whiteness is 85, and the BET test is 1.650m 2 / g.
[0062] Comparative Example 4 The difference from Example 1 is that the particle size of the flame-synthesized titanium niobium oxide powder is too large, with a particle size D50 of 3200 nm and a particle size D90 of 7200 nm.
[0063] Step 1: Dry the titanium niobium oxide powder III (amorphous powder, particle size D50 is 3200 nm, D90 is 7200 nm, impurity content is 6wt%) collected from the front end of the process, and set the drying temperature to 120°C. Anneal the titanium niobium oxide powder to remove carbon and adjust the crystal phase. Use a corundum pot, fill each can with 300g of titanium niobium oxide, cover the corundum pot, but leave a gap to allow the surrounding oxygen to enter the corundum pot, and anneal. During the annealing process, the heating rate is 10°C / min, the temperature is raised to 1000°C, and the temperature is kept for 2h. While heating and keeping the temperature, an oxygen atmosphere is used, and the oxygen flow rate is 3L / min. After annealing, cool to room temperature to obtain a monoclinic phase powder with a purity of 99.9%.
[0064] Step 2: Ball milling is used to crush some agglomerates (hollow spherical particles) in the monoclinic phase powder. First, a small amount of zirconium beads is filled at the bottom of the ball mill, and then the powder is loaded with a ball-to-material ratio of 1:1. The ball mill is tightened to prevent the powder inside from spilling out during rotation. Then, ball milling is performed with a ball mill speed of 500 r / min and a ball mill operation time of 1 h.
[0065] Step 3: Filter press the titanium niobium oxide powder: Use a filter tank to filter press the ball-milled titanium niobium oxide powder, the filtration pressure is 0.3MPa, the filter paper filtration accuracy is 0.45μm, filtration is 1 tank, the filtration time is 30min, the filtration is completed when the water loss rate is 10%, and the anhydrous ethanol flowing out of the filtration is collected.
[0066] Step 4: Drying the titanium niobium oxide powder: The titanium niobium oxide powder with a water loss rate of 10% obtained after filter pressing is put into an oven for drying. The powder needs to be flattened with a scraper, baked in an oven at 70°C for 30 minutes, broken with a glass rod, and then heated to 120°C for 1.5 hours. Take 20g of the dried powder for water loss rate test and whiteness test. The water loss rate is 0%, the whiteness is 84, and the BET test is 0.601m 2 / g.
[0067] The samples of Examples 1-4 and Comparative Examples 1-4 were made into soft-pack batteries: titanium niobium oxide powder was added to N-methylpyrrolidone to prepare a slurry, the slurry was coated on an aluminum foil, and a positive electrode sheet with a thickness of 150 μm was obtained after drying and pressing. A lithium sheet was used as a negative electrode sheet, and the prepared positive electrode sheet, negative electrode sheet and separator were stacked in a Z-shaped stacking manner. After welding, liquid injection, pre-charging, secondary sealing, formation and other processes, a soft-pack battery was obtained, and a back-end test was carried out. The test results are shown in Table 1.
[0068] Table 1
[0069] As shown in Table 1, in Comparative Example 1, the flame-synthesized titanium niobium oxide cannot be transformed from an amorphous powder to a monoclinic phase powder because the annealing temperature is too low. Although a smaller particle size can still be obtained after ball milling, the electrochemical performance of the titanium niobium oxide powder is poor, which is not conducive to application in lithium batteries. In Comparative Example 2, the oxygen flow rate during the annealing process is large, resulting in a final powder particle size that is too large, and the particle size distribution is wider than that of Examples 1-3, and the electrochemical performance of the obtained titanium niobium oxide powder is also poor. In Comparative Example 3, the ball milling material is relatively large, resulting in incomplete powder crushing, which will also cause the final titanium niobium oxide powder particle size to be too large. In Comparative Example 4, the particle size of the flame-synthesized titanium niobium oxide powder is too large, and even if the same post-processing method is used, the powder of the target particle size cannot be obtained, and the electrochemical performance of the titanium niobium oxide powder is poor.
[0070] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A post-treatment method for flame-synthesized titanium niobium oxide powder, characterized in that: The steps include: Step 1: The titanium niobium oxide powder prepared by flame synthesis is an amorphous powder with a particle size D50 of 0.9-3 μm and a D90 of 10-15 μm; the powder is annealed in an oxygen atmosphere at a temperature of 1000-1200° C. for a holding time of 2-3 h to obtain a monoclinic phase powder; Step 2: ball milling to crush the hollow sphere particles in the monoclinic phase powder, with a ball-to-material ratio of 1:1-3 and a ball milling speed of 100-500r / min; Step 3: Perform filter pressing and drying to obtain post-treated titanium niobium oxide powder.
2. The post-treatment method of flame synthesized titanium niobium oxide powder according to claim 1, characterized in that: The impurity content of the titanium niobium oxide powder prepared by the flame synthesis method is 3-6wt%.
3. The post-treatment method of flame synthesized titanium niobium oxide powder according to claim 1, characterized in that: The heating rate of the annealing is 10-20°C / min.
4. The post-treatment method of flame synthesized titanium niobium oxide powder according to claim 1, characterized in that: The oxygen flow rate during the annealing is 3-5 L / min.
5. The post-treatment method of flame synthesized titanium niobium oxide powder according to any one of claims 1 to 4, characterized in that: The annealing conditions are: heating from room temperature to 1000° C. at a heating rate of 10-20° C. / min, keeping the temperature for 2-3 hours, and then cooling to room temperature.
6. The post-treatment method of flame synthesized titanium niobium oxide powder according to claim 1, characterized in that: The ball milling time is 1-3h.
7. The post-treatment method of flame synthesized titanium niobium oxide powder according to claim 1, characterized in that: The pressure of the filter press is 0.2-0.5 MPa, and the time is 20-60 min.
8. The post-treatment method of flame synthesized titanium niobium oxide powder according to claim 1, 6 or 7, characterized in that: The drying temperature is 60-150° C. and the drying time is 1-4 hours.
9. The post-treatment method of flame synthesized titanium niobium oxide powder according to claim 1, characterized in that: The particle size D50 of the post-treated titanium niobium oxide powder is 300-600nm, and D90 is 800-1200nm.
10. Use of the post-treated titanium niobium oxide powder obtained by the method according to any one of claims 1 to 9 in a lithium battery.
Citation Information
Patent Citations
A nanoparticle swirling flame atomization doping synthesis system and its synthesis method
CN110465257B
Titanium-niobium composite oxide-based electrode active material and lithium secondary battery using the same
CN104868108A
Preparation method of electrode material
CN106784773A
Cyclone flame atomization doping synthesis system and method for nanoparticle
CN110465257A
Flame method for preparing micron crystal ball material
CN1149506A